DIVERSIDAD Y COMPOSICIÓN FLORÍSTICA EN UN BOSQUE CON ABUNDANCIA DE NOGAL (Juglans neotropica DIELS) EN CHANCHAMAYO / JUNÍN / PERÚ - Woll, Juan Carlos (2023)
Understanding forest dynamics is fundamental to their ecological restoration. This is particularly important in forests rich in species of commercial value, such as those of the Juglans genus, which known allelopathic effect could have an impact on the diversity of locations where it exists. The objective of this study was to evaluate the floristic composition and tree diversity of a forest dominated by Juglans neotropica Diels, establishing a permanent plot of 100 x 100 m in the Chanchamayo valley. In the plot, all trees were evaluated with DBH ≥ 10 cm. The permanent plot presented 300 individuals, which corresponded to 47 species in 20 families. The Fisher’s Alpha diversity index value was 15.62, and the Shannon-Wiener index value 1.65. These values are notoriously low in comparison with similar sites located in tropical premontane forests referred to in the present work. Due to the allelopathic nature of J. neotropica Diels, it is possible that this condition is a determining factor for the high abundance of this species in the plot and the low tree diversity identified. Since J. neotropica Diels is categorized as endangered by IUCN, the area becomes an important location for its conservation and that of its gene pool.